Experts' views on ḥiyal in Malaysian Islamic banks: the case of tawarruq-based deposit products - Muhammad Izzul Syahmi; Mohammad Taqiuddin Mohamad; Mohd Anuar Ramli (ISRA International Journal of Islamic Finance, 2022)
Purpose - There are two purposes to this study: first, to identify the status of ḥiyal (legal devices) in the offering of deposit products based on the tawarruq contract in the Malaysian Islamic banking industry and second, to identify the reasons for the widespread offering of tawarruq-based deposit products by Malaysian Islamic banks (IBs). Design/methodology/approach - The study uses the qualitative method that involved interviews with Malaysian Sharī'ah experts and Islamic banking operations experts. Findings - The findings show that Malaysian IBs resolved to use the tawarruq munaẓẓam contract in deposit products due to several constraints in the existing banking system and in view of customer preferences. Research limitations/implications - This study solely focuses on tawarruq-based deposit products due to its extensive application in the Malaysian Islamic banking industry. Practical implications - The implication of the study is that more stringent procedures are required in the offering of tawarruq-based deposit products as they are extensively utilised and have sparked controversy among Sharī'ah scholars. Moreover, to retain Malaysia's Islamic banking reputation and trustworthiness, new and less controversial contracts must be developed. Originality/value - This paper discusses the extensive usage of ḥiyal-based contracts such as tawarruq in Islamic banking institutions' deposit products, with justifications from Malaysian Islamic banking experts. The widespread use of the tawarruq munaẓẓam contract in deposit-based product offerings is based on a reasonable view considering the constraints that Malaysian Islamic banking is currently facing, with strict operation procedures by Bank Negara Malaysia to ensure real operations and to avoid fictitious elements. This paper reveals the use of tawarruq munaẓẓam in deposit products which allows the Islamic banking industry to operate effectively under Malaysia's dominant conventional banking system.
Keywords: 330; Ḥiyal; Makhārij; Maṣlaḥah; Salam contract; Tawarruq munaẓẓam